Theory of constraints (TOC) practices of a semiconductor company - Yek, P.N.Y (University Malaysia Sarawak, UNIMAS., 2005)
The main objective of this study is to investigate The Theory of Constrains (TOC) Practices in a Semiconductor Company located in Kuching, Sarawak. The first objective of this study is to identify more superior factors for bottle neck recognition. Second objective is to develop a method to exploit the bottleneck. The third objective is to develop a method to evaluate the bottleneck.